Residential neighborhood as paradigm of development Maribor in the second half of the 20th century - Škratek, Gregor (Journal for Geography, 2014)
This article deals with the paradigm of residential neighborhood on the case of city Maribor, that was typical at the construction of Slovenian cities in the second half of the 20th century. The purpose of this research is to compare residential neighborhoods to each other and to learn about morphological and functional characteristics of the neighborhood at different times in their development. Findings are based on a comparison of three residential neighborhoods in Maribor: neighborhood Metalna, neighborhood along street Gosposvetska cesta and neighborhood S31.